The Effect of Short Movies on Improving Writing Skills in Senior High School Students - Tri Aprilia Suciati; Perdana, Indra; Karani, Elanneri (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study examined the effect of using short movies as a teaching tool on improving writing skills in senior high school students. Writing was often a challenging skill for students, especially in traditional teaching environments, which hindered their creativity and writing proficiency. The integration of multimedia tools, such as short films, offered an innovative approach to enhancing student engagement and writing abilities. This pre-experimental study involved 30 eleventh-grade students from a senior high school in Banjarmasin, Indonesia, who were selected using purposive sampling. Data were collected using pre-and post-tests, focusing on narrative writing tasks before and after exposure to four short movie-based lessons. The results indicated a significant improvement in students' writing scores, with an average increase of 17.8 points. Statistical analysis using paired sample t-tests revealed a significant positive effect (p < 0.05), supporting the hypothesis that short movies could effectively enhance students' writing performance. The study concluded that short films were a valuable educational tool that not only improved writing skills but also motivated and engaged students, making writing tasks more relatable and enjoyable. These findings suggest that incorporating short movies into the curriculum could lead to better writing outcomes in senior high school English education.